1993
DOI: 10.1246/bcsj.66.1294
|View full text |Cite
|
Sign up to set email alerts
|

Facile Oxidative Coupling of Benzene by the Palladium(II) Acetate–Dialkyl Sulfide System

Abstract: By the palladium(II) acetate–dialkyl sulfide system, oxidative coupling of benzene has been achieved at 70 °C, where palladium(II) acetate alone is inactive for the reaction. Effects of alkyl group on the sulfides, molar ratios of sulfide to palladium(II) acetate, and atmosphere of oxygen have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…van Helden and Verberg first described an oxidative homocoupling of benzene in the presence of stoichiometric amounts of PdCl 2 and sodium acetate in acetic acid as the solvent to afford biphenyl . After that, metals such as Hg(II), Tl(III), Fe(III), or Cu(II) and palladium catalysts such as Pd(OAc) 2 , Pd(acac) 2 , and Pd(ETDA) (EDTA = ethylenediaminetetraacetic acid) have been employed in various conditions at high oxygen pressures and temperatures for this homocoupling reaction in a catalytic manner. Recently, protocols for this homocoupling under aerobic oxidation have also been described in the presence of PdCl 2 catalyst, cocatalyst (Zr(OAc) 4 /Co(OAc) 2 /Mn(OAc) 2 /acetylacetone), and AcOH/AcONa as the solvent (Scheme ). , The authors suggested that a peroxocobalt(III) species, Co(III)−OO−Co(III), could be generated in this system, although the exact role of each metallic salt was unclear. Reaction of Pd(0) with this species could give a Pd(II)−peroxo complex.…”
Section: Oxidative C−c Bond Formations Between Two Nucleophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…van Helden and Verberg first described an oxidative homocoupling of benzene in the presence of stoichiometric amounts of PdCl 2 and sodium acetate in acetic acid as the solvent to afford biphenyl . After that, metals such as Hg(II), Tl(III), Fe(III), or Cu(II) and palladium catalysts such as Pd(OAc) 2 , Pd(acac) 2 , and Pd(ETDA) (EDTA = ethylenediaminetetraacetic acid) have been employed in various conditions at high oxygen pressures and temperatures for this homocoupling reaction in a catalytic manner. Recently, protocols for this homocoupling under aerobic oxidation have also been described in the presence of PdCl 2 catalyst, cocatalyst (Zr(OAc) 4 /Co(OAc) 2 /Mn(OAc) 2 /acetylacetone), and AcOH/AcONa as the solvent (Scheme ). , The authors suggested that a peroxocobalt(III) species, Co(III)−OO−Co(III), could be generated in this system, although the exact role of each metallic salt was unclear. Reaction of Pd(0) with this species could give a Pd(II)−peroxo complex.…”
Section: Oxidative C−c Bond Formations Between Two Nucleophilesmentioning
confidence: 99%
“…143 After that, metals such as Hg(II), 144 Tl(III), 145 Fe(III), 146 or Cu(II) 147 and palladium catalysts such as Pd(OAc) 2 , Pd(acac) 2 , and Pd(ETDA) (EDTA = ethylenediaminetetraacetic acid) have been employed in various conditions at high oxygen pressures and temperatures for this homocoupling reaction in a catalytic manner. [148][149][150][151][152][153][154][155] Recently, protocols for this homocoupling under aerobic oxidation have also been described in the presence of PdCl 2 catalyst, cocatalyst (Zr(OAc) 4 /Co(OAc) 2 / Mn(OAc) 2 /acetylacetone), and AcOH/AcONa as the solvent (Scheme 81). 156,157 The authors suggested that a peroxocobalt(III) species, Co(III)-OO-Co(III), 158 could be generated in this system, although the exact role of each metallic salt was unclear.…”
Section: 32mentioning
confidence: 99%
“…Whenever Pd(OAc) 2 proved inactive for oxidative coupling, the Pd(OAc) 2 −dialkyl sulfide was tried instead. The effects of the sulfide alkyl group, the molar ratio of sulfide/Pd(OAc) 2 , and the oxygen atmosphere have been investigated …”
Section: 4 Arene−arene Couplingsmentioning
confidence: 99%